Sustainable aviation technology and operations : research and innovation perspectives - Sabatini, Roberto; Gardi, Alessandro (Aerospace Series, 2024)
Sustainable Aviation Technology and Operations provides a comprehensive and timely outlook of recent research advances in aeronautics and air transport, with emphasis on both long-term sustainable development goals and current achievements.This book discusses some of the most promising advances in aircraft technologies, air traffic management and systems engineering methodologies for sustainable aviation. The topics covered include: propulsion, aerodynamics, avionics, structures, materials, airspace management, biofuels and sustainable lifecycle management. The physical processes associated with various aircraft emissions including air pollutants, noise and contrails are presented to support the development of computational models for aircraft design, flight path optimization and environmental impact assessment. Relevant advances in systems engineering and lifecycle management processes are also covered, bridging some of the existing gaps between academic research and industry best practices. A collection of research case studies complements the book, highlighting opportunities for a timely uptake of the most promising technologies, towards a more efficient and environmentally sustainable aviation future.Key features:Contains important research and industry relevant contributions from world-class experts.Addresses recent advances in aviation sustainability including multidisciplinary design approaches and multi-objective operational optimisation methods.Includes a number of research case studies, addressing propulsion, aerostructures, alternative aviation fuels, avionics, air traffic management, and sustainable lifecycle management solutions.Sustainable Aviation Technology and Operations is an excellent book for aerospace engineers, aviation scientists, researchers and graduate students involved in the field